(3GdEYdGe HhajGJ GdYdeGA GdEYdGes - (3CHh GdYHGS CMeO Hf eMeO GdGejf Hf GdaGVd GdhOGfj GdYHGSj GdQUGaj GdjYbhHjs
(3ChdgG (B:s
(3MeOkG def dg GdHbGA GdOGFe hZjQg dg GdafGA dGRe s
(3BNQgG (B:s
(3bO Je eGQGe GdhOGfj CMeO Ydi GdJeGe Gddg QHi CMeO Udj Ydi GdfHj hBdg dcQGe jGQHfG hGQRb dfG MSf GdNJGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B87 - (3U(B135s
(3GdfSNI HgG MhGTs
(3YdjgG JbjjOGJs
(3hYdi GdeLehYI Jedc HGSe GdoeNJGQ Hf YHOGddg Hf CMeOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B927 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B36 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs